One-step electrochemical synthesis of PEDOT based composites for supercapacitor applications (Rudarsko-geološko-naftni zbornik, 2023)
The aim of this work was to determine the optimal synthesis conditions for the preparation of a poly(3,4-ethylenedioxythiophene) (PEDOT) layer by the electrochemical method from an electrolyte containing graphene oxide (GO) and a sodium dodecylsulfate (SDS) micellar solution. Besides an SDS anion, GO is also incorporated within the PEDOT layer as a negative counter ion. Therefore, this is a one-step electrochemical method for a PEDOT/GO composite layer preparation. The results displayed that PEDOT composites were successfully synthesised by applying a potential in the value range from 0.94 to 1.00 V, and with a synthesis duration of up to 600 s. It was concluded that the optimal concentration of EDOT monomer is 0.02 mol dm-3, and SDS 0.01 mol dm-3. The incorporation of GO into the PEDOT layer improved the polymer response in KCl solution influencing the pseudocapacitive properties, which is significant for its supercapacitor applications. The morphological and structural properties of the obtained layers were characterized by means of scanning electron microscopy and ultraviolet-visible spectrophotometry. The pseudocapacitive properties were determined in a 0.1 mol dm-3 KCl solution by using cyclic voltammetry and electrochemical impedance spectroscopy methods.